(untitled) (Journal of the College of Basic Education, 2023)
Analyze of the topics of geometry and measurement included in upper primary stage mathematics books according to the standards of the mathematics curriculum document The aim of the research is to analyze the topics of geometry and measurement included in the mathematics books of the upper primary stage according to the standards of the mathematics curriculum document. To achieve the aim of the research, the following questions were formulated:- 1- Are the standards of the mathematics curriculum document, geometry and measurement available in the content of the mathematics book for the fourth class primary ? 2- Are the standards of the mathematics curriculum document, geometry and measurement available in the content of the mathematics book for the fifth class primary? 3- Are the standards of the mathematics curriculum document, geometry and measurement available in the content of the mathematics book for the sixth class primary? 4- Are the standards of the mathematics curriculum document, geometry and measurement available in the content of mathematics books prescribed for the primary stage? The researcher adopted the descriptive analytical approach, The research sample consisted of geometry and measurement topics included in the content of upper primary school mathematics books for the academic year (2022-2023), n order to conduct the process of analyzing engineering and measurement topics, a content analysis card was prepared in accordance with the standards of the Mathematics Curriculum Document for Engineering and Measurement, to confirm Its validity after presenting it to a group of arbitrators in mathematics teaching methods and curricula, The list of standards, in its final form, consists of (3) axes and (78) indicators, The topics of geometry and measurement included in the mathematics books prescribed for the upper primary stage were analyzed according to these standards. A sample of the analysis was presented to a number of arbitrators and specialists, and they agreed on the validity of the analysis process. The stability of the analysis was confirmed through the use of two methods of stability, the first is stability over time and the second is stability across analysts. were used Statistical means represented by frequencies and percentages. The results of the research reached:1- The content of the mathematics books for the upper primary stage contains the standards of the curriculum document for geometry and measurement in varying percenting2-The axis of geometric shapes (their concept and representation) achieved the first rank, followed by the axis of measurement (its concept, representation and operations on it) in the second rank, then the axis of geometric measurement and performing operations on it in the third rank in the content of mathematics books prescribed for the upper primary stage, except for the mathematics book for the sixth class of primary3- The mathematics book for the third class of primary ranked first in its inclusion of the standards of the mathematics curriculum document for geometry and measurement, followed by the mathematics book for the second class of primary , then the mathematics book for the first class of primary l n the light of these results, the researcher recommended a number of recommendations, including: making use of the list of mathematics curriculum document standards for engineering and measurement when making a change or development in the mathematics curricula for the upper primary stage, and holding courses and workshops related to the mathematics curriculum document standards for the purpose of informing teachers and specialists about them. A number of proposals were also presented, including: conducting research similar to the current research on other educational stages, and conducting a comparative research between the mathematics books prescribed for the primary stage in Iraq and the mathematics books of international countries in the topics of geometry and measurement l n the light of these results, the researcher recommended a number of recommendations, including: making use of the list of mathematics curriculum document standards for engineering and measurement when making a change or development in the mathematics curricula for the upper primary stage, and holding courses and workshops related to the mathematics curriculum document standards for the purpose of informing teachers and specialists about them. A number of proposals were also presented, including: conducting research similar to the current research on other educational stages, and conducting a comparative research between the mathematics books prescribed for the primary stage in Iraq and the mathematics books of international countries in the topics of geometry and measurement.